Drink combination made from Fenugreek seeds and Phoenix dactylifera to increase prolactin hormone levels in postpartum mothers and its impact on baby weight - Halimah, Siti; Wijayanti, Krisdiana; Taadi, Taadi (MEDISAINS, 2022)
Background: Breast milk is the best leading food for the growth and development of the baby; however, the production of breast milk produced by breastfeeding mothers is still lacking and impacts the baby's weight. One of the efforts is consuming a combination drink of Fenugreek seeds and Phoenix dactylifera containing galactagogue, which has never been done in this study before, to see an increase in breast milk production from indicators of prolactin hormone levels and its impact on baby weight.Purpose: Knowing the effect of giving drinks a combination of Fenugreek seeds and Phoenix dactylifera on the hormone prolactin and its impact on baby weight.Methods: This is an experimental study with a combination design, pretest-posttest, and posttest-only design. Respondents totaled 32 breastfeeding mothers, 16 were given drinks combination of Fenugreek seeds and Phoenix dactylifera, and 16 were given Phoenix dactylifera drinks. The intervention was given for 14 days, and the Mann-Whitney test analyzed prolactin hormone and baby weight using the Independent T-test.Results: Mean levels of the hormone prolactin in the intervention group were higher (279.52 ng/ml) than in the control group (263.31 ng/ml) with p>0.05. The average increase in body weight of infants of the intervention group (606.25 g) was higher than the control group (381.25 g) with a p<0.05.Conclusion: A drink combination made from Fenugreek seeds and Phoenix dactylifera can increase hormone prolactin. However, it is not statistically meaningful, and mothers who consume drinks have babies weighing higher than mothers who only give Phoenix dactylifera drinks.